Answer:
C. 40-4x-12x^2
Step-by-step explanation:
very simple
? – (20 – 4x – 5x2) = 20 – 7x2, so ? = 20 – 7x2 + (20 – 4x – 5x2)
? = 20 – 7x2 + (20 – 4x – 5x2)=20-7x²+20-4x-5x²=40-12x²-4x
Answer:
f(g(-8)) = -26
Step-by-step explanation:
Given:
f(x)=2x and g(x)=2x+3
Required:
f(g(-8))=?
Solution:
First we will find g(-8)
g(x) = 2x+3
g(-8)= 2(-8)+3
= -16 + 3
= -13.
so, g(-8) = -13
Now, for calculation f(g(-8)) we can put the value of g(-8) i.e, -13
so, f(x) = 2x
f(-13) = 2(-13)
= -26
so, f(-13) = -26
and f(g(-8)) = -26
P should equal 3. hope this helps.
Answer: C
Step-by-step explanation:
Rejecting the null hypothesis means we've found a significant difference in the means. That means the probability that we'd see means so far apart by chance is less than our threshold of significance.